Sweet or not: Nudging toward healthier food choices for children using information - Nguyen, Trang; de Brauw, Alan; Van den Berg, Marrit (International Food Policy Research Institute, 2021)
It is of public health interest to nudge children toward healthier food choices such as beverages with less sugar. We conducted a field experiment in peri-urban Viet Nam to evaluate the effects of information and cognitive dissonance arousal on children’s food choice. More than 1200 primary school children were randomly assigned into three groups: control, health information, and health information plus hypocrisy inducement – a way to raise cognitive dissonance by illustrating the gap between what people know they should do (socially desired behaviors) and what they actually did (transgressions). We find that health information raised the likelihood of selecting milk with less sugar by around 30 percent, compared with the control group. Hypocrisy inducement does not make an additional contribution to healthier food choice in our sample. The treatment effects decline with the delay between the treatment and behavioral choice. We discuss the practical implications of our findings for short-term intervention field studies.